Evaluation of a Low-Cost Greenhouse for Controlled Environment Cultivation of Sweet Pepper - Omobowale, M. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Sustainable agriculture is critical towards paving a way for year-round production and supply of food all year round. Cultivation of fruits and vegetables are vital due to high demand and nutritional values it provides to consumers. The rising global population especially in developing countries require other alternatives for sustainable crop production. Cultivation in controlled environments using functional and durable greenhouse structures presents an option. A low-cost greenhouse was designed and constructed in Ibadan, Nigeria using locally available materials was evaluated. Afrormosia wood was used in constructing the frame while polyethylene of 2.5 mm thickness was used as sheathing material for the walls. The floor which covered an area of 24 m2 was made of porous concrete of batching mixture 1:4 (cement to gravel) while the wall was 4 m high. Ventilation was passive with a vent area equal to 25% of total surface area; made up of 20% at the wall area and 5% as the roof vent. The roof was pitched at a 18° slope to allow easy drainage of rain water. Sweet pepper (Capsicum annuum, Cabernet) seeds procured Burpee Seeds USA were cultivated with the aid of planting pots within the greenhouse in comparison with those planted in the open field for a duration of eight weeks. Evaluation was based on crop growth and yield parameters correlated with solar radiation, temperature and relative humidity in the greenhouse and ambient environments, respectively using randomized complete block design. Data were subjected to descriptive and correlation analysis. Peak temperature and RH were 31.1°C and 91.1% respectively within the greenhouse in comparison with 29.7°C and 89.7% respectively outside. Peak solar radiation was 413.4 W/m2 in the greenhouse compared to 690.3 W/m2 in the ambient. Growth parameters showed that the crops in the greenhouse performed optimally when compared with plants in the open field with a yield of 18.1 t/ha in the greenhouse compared with no-yield recorded in the open field. Utilization of greenhouses in crop cultivation can help to mitigate the problem of food shortage.